Sildenafil preserves lung endothelial function and prevents pulmonary vascular remodeling in a rat model of diastolic heart failure - Yin, Jun; Kukucka, Marian; Hoffmann, Julia; Sterner-Kock, Anja; Burhenne, Jürgen; Haefeli, Walter E.; Kuppe, Hermann; Kübler, Wolfgang Michael (Circulation. Heart failure, 2011)
Background: Pulmonary hypertension as a frequent complication of left heart disease (PH-LHD) is characterized by lung endothelial dysfunction and vascular remodeling. Although PH-LHD contributes to morbidity and mortality in heart failure, established therapies for PH-LHD are lacking. We tested the effect of chronic sildenafil treatment in an experimental model of PH-LHD. - Methods and Results: In Sprague-Dawley rats, PH-LHD was induced by supracoronary aortic banding. Oral sildenafil treatment (60 mg/kg daily) was initiated after 7 days, and lung endothelial function (n=5), vascular remodeling, and right ventricular function (n=11 each) were analyzed 9 weeks after banding. As compared with sham-operated controls, aortic banding induced pulmonary hypertension and lung endothelial dysfunction evident as lack of endothelial nitric oxide production and endothelium-dependent vasodilation. These changes were associated with an increased pulmonary vascular resistance, medial thickening, and biventricular cardiac hypertrophy. Sildenafil treatment largely attenuated these pathological changes and was not associated with detectable adverse effects pertinent to lung vascular barrier function, edema formation, or systemic hemodynamics. - Conclusions: Our data identify sildenafil as a promising therapy for PH-LHD. In light of its documented protective effects at the myocardial level in heart failure, sildenafil presents a particularly attractive strategy in that it simultaneously targets cardiac remodeling and secondary PH-LHD.